Duration of an induced resistance of sheep to acute poisoning by Crotalaria retusa seeds - Lisanka Angelo Maia (Ciência Rural, 2014)
The aim of this study was to determine the duration of the resistance after the end of the ingestion of non-toxic doses of Crotalaria retusa seeds. Ten sheep were divided into 3 groups of 3 animals each and a control group with 1 sheep. To induce resistance, sheep in groups 1, 2 and 3 received 20 daily doses of 2g kg-1 of C. retusa seeds, followed by 7 daily doses of 4g kg-1. To determine the duration of resistance the sheep in groups 1, 2 and 3 were challenged orally, 3, 7 and 15 days, respectively, after receiving the last dose of 4g kg-1, with a single dose of 5g kg-1. Sheep of groups 1 and 2 did not develop overt signs of poisoning. Two sheep of group 3, challenged 15 days after the end of the resistance induction period, showed signs of acute poisoning and died. These results suggest that the induced resistance of sheep to acute poisoning by C. retusa seeds is of short duration, from 7 to 15 days.